Efficacy of Radium-223 in Bone-metastatic Castration-resistant Prostate Cancer with and Without Homologous Repair Gene Defects - Velho, Pedro Isaacsson (Eur Urol, 2018)
BACKGROUND: Pathogenic mutations in genes mediating homologous recombination (HR) DNA repair are present in 20-30% of men with metastatic castrate-resistant prostate cancer (mCRPC). Radium-223 is a bone-seeking α-emitter that induces double-strand DNA breaks, thereby killing cancer cells in the bone microenvironment. OBJECTIVE: To evaluate the potential impact of germline or somatic HR-deficiency (HRD) mutations on radium-223 efficacy in bone mCRPC. DESIGN, SETTING, AND PARTICIPANTS: This is a retrospective single-institution study. Medical records of 190 mCRPC patients for whom germline and/or somatic DNA sequencing data were available were reviewed. Of these patients, 28 had received standard-of-care radium-223 at Johns Hopkins between February 2013 and February 2018. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: Alkaline phosphatase (ALP) responses and time-to-ALP-progression were the coprimary endpoints. Prostate-specific antigen (PSA) responses, overall survival (OS), and time to next systemic therapy were also evaluated. RESULTS AND LIMITATIONS: Of the 28 patients included, 10 men (35.7%) had a germline/somatic HRD mutation (three in BRCA2, and one each in ATM, ATR, CHEK2, FANCG, FANCI, FANCL, and PALB2) and 18 (64.3%) did not. Men with HRD mutations (HRD+) had numerically lower ages (66 vs 73 yr, p = 0.25), more soft-tissue metastases (50% vs 38%, p = 0.43), and higher baseline ALP levels (130 vs 108 U/l, p = 0.84). Compared with HRD(−) men, HRD(+) patients showed greater ALP responses (80% vs 38%, p = 0.04), longer time to ALP progression (median10.4 vs 5.8 mo, hazard ratio [HR] 6.4, p = 0.005), and a trend toward longer OS (median 36.9 vs 19.0 mo, HR 3.3, p = 0.11). PSA responses (0% vs 0%, p > 0.99) and time to next systemic therapy (HR 1.5, p = 0.39) were similar between the two groups. Results are limited by the retrospective nature of the analysis and the small sample size. CONCLUSIONS: In this exploratory study, bone-metastatic mCRPC patients with inactivating HRD mutations demonstrated significantly improved ALP responses and time to ALP progression. These results should motivate prospective validation of the “synthetic lethality” hypothesis between HRD mutations and radium-223 activity.